2016
DOI: 10.1097/md.0000000000002948
|View full text |Cite
|
Sign up to set email alerts
|

Is MDM2 SNP309 Variation a Risk Factor for Head and Neck Carcinoma?

Abstract: Murine double minute-2 (MDM2) is a negative regulator of P53, and its T309G polymorphism has been suggested as a risk factor for a variety of cancers. Increasing evidence has shown the association of MDM2 T309G polymorphism with head and neck carcinoma (HNC) risk. However, the results are inconsistent. Thus, we performed a meta-analysis to elucidate the association.The meta-analysis retrieved studies published up to August 2015, and essential information was extracted for analysis. Separate analyses on ethnici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Difference between survival groups was not significant, but MDM2 T/T survival was 65.6% and T/G survival was 46.0% at 1631 days' post-surgical operation (p = 0.13). Zhua X. et al results indicate that homozygous G/G alleles of MDM2 SNP309 may be a low-penetrant risk factor for HNSCC, and G allele may confer nasopharyngeal Canter susceptibility [26]. Data were confirmed in the Asian population: in a study of 103 patients, the G/G genotype of MDM2 SNP309 was associated (p = 0.032) with an earlier onset of HNSCC.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Difference between survival groups was not significant, but MDM2 T/T survival was 65.6% and T/G survival was 46.0% at 1631 days' post-surgical operation (p = 0.13). Zhua X. et al results indicate that homozygous G/G alleles of MDM2 SNP309 may be a low-penetrant risk factor for HNSCC, and G allele may confer nasopharyngeal Canter susceptibility [26]. Data were confirmed in the Asian population: in a study of 103 patients, the G/G genotype of MDM2 SNP309 was associated (p = 0.032) with an earlier onset of HNSCC.…”
Section: Discussionmentioning
confidence: 92%
“…Methylenetetrahydrofolate reductase (MTHFR) is an important enzyme in folate metabolism [24]. The C677T SNP in MTHFR (rs1801133), which regulates the release of active folate in the body, may have reduced activity [25,26]. Epidemiological evidence suggests that the SNPs encoding the enzymes involved in folate metabolism may increase the risk of head and neck cell carcinoma (HNSCC) by altering DNA methylation synthesis and genomic stability [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, authors suggested that this polymorphism may modulate cancer risk in combination with p53 and p73 polymorphisms. More interestingly, a recent meta-analysis by Zhuo et al [57] also suggested that homozygote GG alleles of MDM2 SNP309 may be a low-penetrant risk factor for HNC, and G allele may confer nasopharyngeal cancer susceptibility.…”
Section: Mdm2 and Its Association With P53mentioning
confidence: 99%
“…Based on this tightly balanced negative feedback mechanism; it is understandable that any genetic polymorphism in MDM2 can also alter p53 functional levels. A number of reports have highlighted this fact in oral cancers especially via one intronic polymorphism (rs2279744) in MDM2 leading to its induced expression [ 26 ].…”
Section: Genetic Factors and Signaling Pathways Involved In Therapeutic Resistance Of Oral Cancermentioning
confidence: 99%